Poly(glycidyl methacrylate) coated dual mode upconverting nanoparticles for neuronal cell imaging. (3rd June 2016) - Smith, Nicole M.; Ho, Diwei; Munshi, Alaa M.; House, Michael J.; Dunlop, Sarah A.; Fitzgerald, Melinda; Swaminathan Iyer, K.
Abstract : NaGdF4 :Yb, Er nanoparticles with a functional poly(glycidyl methacrylate) (PGMA) coating, as a biocompatible multimodal formulation for neuronal cell imaging. Abstract : Lanthanide-doped upconversion nanoparticles are promising dual mode near-infrared (NIR) and magnetic resonance imaging (MRI) bioimaging agents. In this communication we report the utility of NaGdF4 :Yb, Er nanoparticles with a functional poly(glycidyl methacrylate) (PGMA) coating, as a biocompatible multimodal formulation for neuronal cell imaging.